The influence of sustainable leadership and sustainable performance through frugal innovation in tourist villages in Indonesia - Ratih Anggraini; Karen Kho; Dessy Aliandrina (Universitas Merdeka Malang, 2023)
Tourism village is one of the tourist attractions that have the potential to increase development in Indonesia tourism. Tourism village have natural, cultural and historical attractions to catch tourist’s attention. The involvement of local people, government and tourism village manager in managing village resources is needed so the tourism village can be sustainable. This research aims to know how to improve the development of village tourism through frugal innovation, sustainable leadership, and sustainable performance and how they influence and relate with each other to tourism village. This research used PLS-SEM for testing hypotheses and significance between variables amd used snowball sampling as a data collection method in this research. Based on the result of data testing, the research results show there’s positive effect between sustainable leadership and sustainable performance with frugal innovation as mediation variable. Which means that frugal innovation has be a success role of sustainable leadership to achieve sustainable performance. Therefore, the manager of village tourism can plan the village tourism’s future by leading the members in creating value to the village’s resources through frugal innovation and maintaining optimal performance.